153 RARE CASE OF INFECTED SPLENIC HEMATOMA. (1st January 2005) - Godkar, D.; Recco, R.
Abstract : Background: Splenic hematoma is a relatively benign condition as majority of them are spontaneously absorbed and rarely warrant therapy. Rarely, they can get infected; a condition that is difficult to diagnose and is associated with significant morbidity and mortality if left untreated. The key to diagnosis is having a high degree of suspicion in the febrile patient with abdominal pain, especially in the setting of immunosuppression, associated systemic illness, or known prior splenic injury. Computerized tomography (CT) scan is currently the modality of choice for diagnosis of splenic collections. Definitive therapy with percutaneous drainage or splenectomy with adequate antibiotic cover is warranted in these conditions. We present the second reported case of secondary infection of a preexisting splenic hematoma. Case Report: Fifty year old Hispanic male, intravenous drug abuser, who had a history of fall six weeks prior to presentation was admitted with fever and left sided abdominal pain. Laboratory data showed leukocytosis; CT scan of abdomen showed splenic collection with air-fluid level which was initially thought to be an abscess but turned out to be an old hematoma on aspiration. Patient grew Enterococcus faecalis in the blood as well as the aspirate and was also found to have aortic valve vegetation on transesophageal echocardiogram. He was successfully treated with percutaneous drainage and intravenous antibiotics as demonstrated by clinical improvement and gradual reduction to total resolution of the hematoma in question on serial CT scans. Teaching Point: Approach to a patient with intrasplenic collection, differential diagnosis of splenic hematoma, and modalities of treatment in a case of infected splenic hematoma have been discussed.